2009
DOI: 10.1179/174313209x444008
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial thrombolysis for acute central retinal artery occlusion

Abstract: Intra-arterial thrombolysis could obviously improve the short- and long-term visual function for patients with acute central retinal artery occlusion within 6 hours of symptom onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Two large reviews [52, 53] and several observational studies [31, 54, 55] have suggested that thrombolysis in the treatment of CRAO may improve the visual acuity with few serious complications. However, data from a large multicentre randomised study using intra-arterial thrombolysis [56••], and another randomised study using intravenous thrombolysis [30•] have failed to show an improvement in the visual acuity.…”
Section: Treatmentmentioning
confidence: 99%
“…Two large reviews [52, 53] and several observational studies [31, 54, 55] have suggested that thrombolysis in the treatment of CRAO may improve the visual acuity with few serious complications. However, data from a large multicentre randomised study using intra-arterial thrombolysis [56••], and another randomised study using intravenous thrombolysis [30•] have failed to show an improvement in the visual acuity.…”
Section: Treatmentmentioning
confidence: 99%
“…Hence, there is no consistent conclusion on the tolerance time of retinal ischemia in humans, which need further study. In our previous study and other respective case series and cohort studies, it was concluded that IAT could improve visual function in patients with acute CRAO within 6 hours of symptom onset (9,14–16). This study further confirmed that IAT may partially improve visual acuity within 16 h of symptom onset, which may be associated with incomplete ARI having a certain percentage.…”
Section: Discussionmentioning
confidence: 94%
“…No control group. Small sample sizeZhang et al57, 200949<6Urokinase 626,000 units mean dose. Systemic heparin during procedure.…”
Section: Resultsmentioning
confidence: 99%